Effects of anserine on oxidative stress and on cell barrier integrity in methylmalonic aciduria - Köpfer, Felix; Bartosova, Maria; Fleming, Thomas; Pfeffer, Tilman; Okun, Jürgen G.; Kölker, Stefan; Hoffmann, Georg F.; Schmitt, Claus P.; Morath, Marina; Peters, Verena (Scientific reports, 2025)
Kidney damage in individuals with methylmalonyl-CoA mutase deficiency (mut0) results from metabolic and oxidative stress, and disrupted mitochondrial homeostasis. Anserine, known for its antioxidant properties and protective effect on cell barrier integrity of endothelial and epithelial kidney and vascular cells, may offer therapeutic potential for chronic disorders. This study explored anserine’s effects on immortalized kidney tubular epithelial cells (iKTEC) from mut0 patients. Compared to healthy controls, iKTEC from mut0 patients showed reduced cell viability, antioxidant capacity, oxygen consumption, and ATP production. Expression of the tight junction scaffolding protein zonula occludens-1 (ZO-1) was increased in mut0 cells compared to control while transepithelial resistance (TER), and dextran transport (10 kDa) remained unchanged. Anserine treatment restored antioxidant capacity and normalized ZO-1 expression but had no effect on TER or dextran transport. Additionally, cell viability, mitochondrial respiration, and ATP production were unaffected by anserine. Metabolic stress induced by high protein load or disease-associated branched-chain amino acids did not worsen mitochondrial dysfunction or epithelial integrity, and anserine exposure showed no further effects. In conclusion, anserine showed promise in restoring antioxidant capacity in iKTEC from mut0 patients, highlighting its potential as a therapeutic agent to mitigate ROS, although its effects on mitochondrial function and epithelial integrity warrant further investigation.
Gesehen am 15.01.2026